EFEKTIVITAS PENGGUNAAN MEDIA WORDWALL TERHADAP MOTIVASI BELAJAR DAN PEMAHAMAN MATERI MATEMATIKA SISWA SMA NEGERI 3 BANGKALAN - Astuti, Sri Yuni; Huda, Nuril; Utami, Sri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the effectiveness of the use of wordwalls on learning motivation and understanding of mathematics material of students of SMA Negeri 3 Bangkalan. The research method used is quantitative using a quasi-experimental design research design with the type of Pretest-Posttest Control Group Design. This study uses an instrument in the form of a questionnaire to motivate students to learn and an instrument in the form of questions to measure student understanding. The population in this study is the population used in this study, namely SMA Negeri 3 consisting of 216 students. This study took a sample of 2 classes of 36 students each. The sampling technique in this study is using random sampling. Data testing uses SPSS IMB statistics. The results of the study are 1. Wordwall is effective in increasing the learning motivation of SMA Negeri 3 Bangkalan students with test results getting a significance value of 0.000 < 0.05. 2. Wordwall is effective in improving the understanding of the material of SMA Negeri 3 Bangkalan students with test results getting a significance score of 0.000 < 0.05.